The Choice Between Public and Private Debt by Russian Companies at Different Stages of the Life Cycle - RossokhinVladimir; RyabovaElena (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2020)
The problems of formation of the company’s capital structure to date have already been studied well. A large number of theoretical papers and empirical studies devoted to this issue have been published. However, managers are confronted not only with the question of the optimal balance between equity and debt capital, but also with the choice of debt structure in the presence of several of its sources, such as public and private debt. This is a new paradigm in corporate finance. On the one hand, companies are not always ready to issue listed securities at the initial stages of their activity. On the other hand, raising funds in open markets has several advantages. With the help of public debt, one can attract a sufficiently large amount of financial resources with a lower cost in comparison with private borrowing. At the same time, as a rule, the public debt is not secured by the assets in the proper amount. According to the author’s opinion, in dealing with this question, companies can take into account not only the current state of the company and its financial indicators, but also the stages of the life cycle, since each of them has its own development features. The purpose of this study is to analyze whether life cycle stages and other financial indicators of a company affect the choice of a source of borrowed capital (private or public debt), thereby to contribute to the development of this research direction. The objects of study are Russian companies. In the empirical part of the study, the binary choice model had been applied. The sample size is 1,818 companies, the financial statements for three years were used. The stages of the organization’s life cycle were calculated by the method of V. Dickinson. A number of control variables were also included in the model. The results of empirical analysis indicate that the company decides to issue public debt, regardless of the stage of the life cycle. This allows us to conclude that the company, when conceptually resolving the question about the structure of borrowed capital, relies on economic indicators such as profitability, size of the company, structure of assets and financial leverage. Understanding this fact can also help potential investors in making investment decisions to form conservative portfolios.